Exploration of environmentally friendly marine power technology -ammonia/diesel stratified injection. (20th December 2022) - Liu, Long; Wu, Yue; Wang, Yang; Wu, Jie; Fu, Shiyi
Abstract: Carbon emissions are causing a series of environmental problems, seriously threatening the survival and health of human beings, of which the shipping industry accounts for a significant part. Ammonia is a promising carbon-free alternative fuel for carbon emission reduction of marine engines, while the specific application method remains to be discussed. This study explores a potential novel ammonia-diesel stratified injection technology for the application of low-carbon ammonia fuel on marine engines to meet future low-carbon emission regulations. The results illustrate that this strategy can achieve similar engine power as conventional diesel engines and greatly reduce the CO2 and NO x emissions. The energy ratio of ammonia fuel can be as high as 99%, due to the precise delivery of ammonia to the pilot fuel combustion zone, and the NO x emissions can meet Tier III emission standards at 100% load without any after-treatment because of the heat absorption of ammonia vaporization. Meanwhile, the addition of matching pilot fuel injectors can be avoided to save retrofit and material costs. In addition, the effect of various injection strategies, such as pilot diesel energy proportion, multiple stratified injection and injection pressure, on power and emissions were investigated. The result demonstrated that increasing the injection pressure and pilot diesel proportion can both improve the IMEP but also increase the NO x emissions. While multiple stratified injection has little effect on power and emissions. On the whole, the strategy with high injection pressure and less pilot fuel is the optimal solution to achieve high IMEP, low NO x and carbon emissions. Graphical abstract: Image 1 Highlights: ● Ammonia and diesel stratified injection can facilitate the application of ammonia. ● This strategy can greatly reduce CO2 and NO x emissions while increasing IMEP. ● The energy replacement ratio of ammonia can be as high as 99%. ● This strategy can reduce engine modification and save costs.